Changes in behavior patterns or demographic structure? Re-estimating the impact of higher education on the average age of the first marriage - Lai, Ting; Huang, Yiheng; Xiong, Jinwu (Frontiers in Psychology, 2023)
During the last few decades, China implemented college enrollment expansion to accelerate the process of urbanization. However, this policy may lead to a consequence of delaying the age of first marriage, which in turn results in the age of the population. Most existing papers confused the total impact of higher education on the average age of first marriage with the influence on individual’s behavior change on the age of first marriage and thus led to overestimating the delayed effect of higher education on the age choosing behavior of first marriage. The present paper re-estimated the impact of higher education on the average age of first marriage in China with both extensive and intensive margins using the duration model. In addition, the effect of higher education on the average age of first marriage was quantified after removing macroeconomic factors. The results show that changes in either the demographic structure or behavior patterns due to higher education explain 63.41% or 36.59%, respectively, of the average marriage age delay. We also found that after controlling for demographic structure and macro factors, 3 years or more of higher education would only delay the time of choosing to enter the first marriage by 0.84 years. Thus, we conclude that higher education does not completely squeeze the time of marriage, and the expansion of college enrollment could improve social and economic benefits.